No differences in physical activity between children with overweight and children of normal-weight - Janneke van Leeuwen; Bart W. Koes; Winifred D. Paulis; Patrick J. E. Bindels; Marienke van Middelkoop (BMC, 2020)
Abstract Background The aim of this study was to investigate the differences in objectively measured physical activity and in self-reported physical activity between overweight and normal-weight children. Methods Data from a prospective cohort study including children, presenting at the participating general practices in the south-west of the Netherlands, were used. Children (aged 4-15 years) were categorized as normal-weight or overweight using age- and sex specific cut-off points. They wore an ActiGraph accelerometer for one week to register physical activity, and filled out a diary for one week about physical activity. Results A total of 57 children were included in this study. Overweight children spent significantly less percentage time per day in sedentary behavior (β − 1.68 (95%CI -3.129, − 0.07)). There were no significant differences in percentage time per day spent in moderate to vigorous physical activity (β 0.33 (− 0.11, 0.78)). No significant differences were found between children of normal-weight and overweight in self-reported measures of physical activity. Conclusions Overweight children are not less physically active than normal-weight children, which may be associated with the risen awareness towards overweight/obesity and with implemented interventions for children with overweight/obesity.